2013
DOI: 10.4067/s0718-95162013005000068
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fresh and air-dried biosolids as amendments for remediation of acidic and metal-polluted soils: A short-term laboratory assay

Abstract: Biosolids have been used as amendments on mine degraded soils for in situ immobilization of metals, neutralization, and improvement of nutritional, microbiological, and physical characteristics to reestablish a self-sustaining plant community. Fresh and air-dried biosolids have been used but dried ones are preferred as they are cheaper to transport, contain less pathogens and are much easier to handle. The same efficacy has been assumed for both biosolids. The study evaluated the effects of fresh and air-dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Organic carbon mineralization has been studied in soils amended with different types of winery wastes (Bustamante et al, 2007(Bustamante et al, , 2010; Mosse et al, 2012). The effect of wastes and other organic matter sources application to the soil on organic carbon mineralization can be quite variable, and increases (Ginocchio et al, 2013;Hasbullah and Marschner, 2016) and decreases (Meli et al, 2002) have been reported. The short-term increases or decreases in soil organic carbon mineralization caused by the organic matter amendments are defined as positive or negative priming effects (Kuzyakov et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Organic carbon mineralization has been studied in soils amended with different types of winery wastes (Bustamante et al, 2007(Bustamante et al, , 2010; Mosse et al, 2012). The effect of wastes and other organic matter sources application to the soil on organic carbon mineralization can be quite variable, and increases (Ginocchio et al, 2013;Hasbullah and Marschner, 2016) and decreases (Meli et al, 2002) have been reported. The short-term increases or decreases in soil organic carbon mineralization caused by the organic matter amendments are defined as positive or negative priming effects (Kuzyakov et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This partitioning approach assumes that dissolved metals are mobile and could possibly be taken up by plant roots or otherwise be interacting with various soil organisms ( Sauvé et al, 2000). Finally, the free Cu 2+ pool is considered to be the primary bioavailable form of soil Cu ( Thakali et al, 2006; Ginocchio et al, 2013), and the best indicator of Cu phytotoxicity ( Sauvé et al, 1998; Oliver et al, 2005). Therefore, discerning among the different pools of Cu is crucial in evaluating the potential environmental and human health risk.…”
Section: Introductionmentioning
confidence: 99%
“…En algunas áreas de la cuenca, los suelos de uso agrícola presentan elevados niveles de metales como cobre y plomo, los cuales estarían asociados a las emisiones proveniente de fundiciones y termoeléctricas (Aguilar et al 2011, Ginocchio et al 2013, González et al 2014). Los estudios de toxicidad en esta zona se han realizado mediante bioensayos de toxicidad de reproducción, crecimiento y biomarcadores moleculares.…”
Section: Introductionunclassified